(untitled) (Al-Academy, 2024)
Baghdad The historical event has a very important role and has a significance related to the determination of space-time as one of the basic factors for understanding design at the conceptual level, and the integration of design with a specific time and place helps in achieving balance and interaction between the elements within the space and enhances the understanding of identity and the general vision of the place, and from this point of view the research problem was the following question: "What are the mechanisms for achieving communication in historical spaces and what did the formation in them in space?" The objective of the research can be determined by: Detecting the internal spaces that witnessed historical events throughout modern local history, and finding design foundations to preserve these spaces, including their material and emotional connotations that achieve communication through their components, the current research included two sections, the first topic is communication through the components of the internal space, the second topic is the levels of achieving space-time communication in the internal space, while the researchers used the descriptive approach to analyze the research model in his research procedures for their compatibility with the requirements of his research and the achievement of the objectives, While the current research community included local heritage cafes in Baghdad, and a heritage café was chosen intentionally (Al-Zahawi Café Al-Rashid (The researchers prepared an analysis form and reached the most important conclusions: 1. The communicative dimension is the ways and means through which the design objectives of the café can be achieved,2. Space-time communication is the apparent verifier between the café and its users, and it appears through the extent to which the café’s patrons accept and react towards the services and activities provided by the café